Biotransformation of organic acids to their corresponding alcohols by Thermoanaerobacter pseudoethanolicus. (June 2019) - Scully, Sean M.; Brown, Aaron; Ross, Andrew B.; Orlygsson, Johann
Abstract: Higher order alcohols, such as 1-butanol and 1-hexanol, have a large number of applications but are currently prepared from non-renewable feedstocks. Here, the ability of Thermoanaerobacter pseudoethanolicus to reduce short-chain fatty acids to their corresponding alcohols using reducing potential generated by glucose catabolism with yields between 21.0 and 61.0%. 13 C-labelled acetate, 1-propionate and 1-butyrate demonstrates that exogenously added fatty acids are indeed reduced to their corresponding alcohols. This mode of producing primary alcohols from fatty acids using a thermophilic anaerobe opens the door for the production of such alcohols from low-value materials using an inexpensive source of reducing potential. Graphical abstract: Image 1 Highlights: T. pseudoethanolicus converts C3-C6 fatty acids to their corresponding alcohols. 33.0% of 1-propionate is converted to 1-propanol during glucose fermentation. 55.6% of 1-butyrate is converted to 1-butanol during glucose fermentation. 33.5% of 1-hexanoate is converted to 1-hexanol during glucose fermentation. 13 C1-labelled propionate and butyrate show conversion to 1-propanol and 1-butanol.